Ireland: 1641 : Contexts and reactions - Ohlmeyer, Jane H.; Ó Siochrú, Micheál, 1966- (Studies in early modern Irish history., 2013)
The 1641 rebellion is one of the seminal events in early modern Irish and British history. Its divisive legacy, based primarily on the sharply contested allegation that the rebellion began with a general massacre of Protestant settlers, is still evident in Ireland today. Thousands of witness testimonies (the 1641 Depositions) housed in Trinity College Dublin became central to one of the most protracted and bitter of Irish historical controversies. This controversy has never been satisfactorily resolved as successive generations invented and re-invented the past in response to contemporary political developments. Propagandists, politicians and historians all exploited the surviving evidence at different times to justify their implacable hostility towards Irish nationalism and the Catholic religion. The 1641 'massacres', therefore, like King William's victory at the Boyne (1690) and the Battle of the Somme (1916) played a key role in creating and sustaining a collective Protestant/British identity in Ulster, in much the same way that the subsequent Cromwellian conquest in the 1650s helped forge a new Irish Catholic national identity. The original and wide-ranging themes chosen for this volume, along with the high standard of the contributions from leading international scholars, will ensure that this edited collection becomes required reading for all those interested in the 1641 Rebellion, as well as the history of early modern Ireland and Europe. It will also appeal to those engaged in early colonial studies in the Atlantic world and beyond, as the volume adopts a genuinely comparative approach throughout, examining developments in a broad global context.